PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR - Supriyadi; Nina Kurniah (DIADIK, 2024)
This study aims to describe the application of the picture and picture type cooperative learning model and describe the effectiveness of applying the picture and picture type cooperative learning model to increase the responsibility and learning achievement of students in class V science subjects at SD Negeri Cluster 3 Lubuk Pinang. The research designs used are Classroom Action Research (PTK) and Quasi-Experimental Research. The subjects in this study were class V students of Cluster 3 Lubuk Pinang in the odd semester of the 2022/2023 academic year. The number of students for the PTK class is 21 people, the experimental class is 23 people and the control class is 21 people. The data collection method in this study used teacher activity observation sheets applying picture and picture type cooperative learning models, responsibility observation sheets and final student learning tests. Data analysis used an average score and a t-test consisting of a different test between cycles and a different test of two unrelated samples. The results showed that: (1) the application of a picture and picture type cooperative learning model can improve students' attitudes of responsibility; (2) The application of a picture and picture type cooperative learning model can improve student learning achievement; (3) The application of the picture and picture type cooperative learning model is very effective in improving students' attitudes of responsibility and learning achievement in class V science subjects at SD Negeri Cluster 3 Lubuk Pinang Mukomuko